Development of Abacus Training Management in the Artificial ‎Intelligence Era - Elice, Deti; Patimah, Siti; Pahrudin, Agus; Koderi; Fauzan, Ahmad; Yustiasari Liriwati, Fahrina (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The growing reliance on AI-driven technologies has raised critical concerns about the decline in students’ abilities in critical thinking, logical reasoning, and motor skills. In response, this study investigates the potential of abacus learning a traditional method that stimulates both hemispheres of the brain by engaging both hands simultaneously to mitigate these challenges. The primary objective is to develop and evaluate an abacus training management model that strengthens the instructional competence of Madrasah Ibtidaiyah teachers, enabling them to implement abacus-based learning effectively within the context of modern educational demands. The research was conducted at Madrasah Ibtidaiyah Negeri Bandar Lampung using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through surveys, interviews, and documentation to support the design, development, and validation of the training model. Expert assessments demonstrated high feasibility: material experts rated the model at 88.75%, and media experts at 92.5%. Additionally, teachers who participated in the training assessed its effectiveness at 85%, indicating strong usability. Quantitative analysis using a t-test revealed a t-observed value of 44.737, significantly exceeding the t-critical value of 2.069 at a 0.05 significance level. This confirms that the model is statistically effective in improving teachers’ abacus teaching skills. These findings reaffirm the continued relevance of traditional tools like the abacus in an era dominated by artificial intelligence. The study concludes that integrating such manual learning strategies can complement digital advancements. Future research is recommended to explore this model’s application across varied educational settings and learner demographics.